Industry 5.0 narrative: utopia and reality - Aveni, Alessandro (Revista JRG de Estudos Acadêmicos, 2023)
The paper analyses INDUSTRY 5.0 definition and its narrative on a broad and didactical discussion to explain and clarify is better thanking care of the narrative, political fashions, and gurus. We need to start with figures. A start should be a deep understanding of the information economy and a critique of the INDUSTRY 4.0 definition. The sustainable development and human wellbeing narrative is an umbrella for discussion used especially today as political goals. But when we seek global indexes, it is easy to see how is manipulated the general narrative. The result and the suggestion of the paper are to change the horizon and the goals of the new INDUSTRY 5.0 narrative into a new Social and environmental development model starting from the economics drivers and avoiding the false narrative of a technology or fake environmental ideology-driven pink future